2010
DOI: 10.5009/gnl.2010.4.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Serum YKL-40 as a Tumor-Specific Marker of Hepatobiliary Malignancies

Abstract: Background/Aims: Serum YKL-40 has been linked to several human cancers. We investigated the potential role of serum YKL-40 as a marker of hepatobiliary malignancies. Methods: Archived serum samples of patients undergoing liver transplantation evaluation at the Mayo Clinic Rochester were used to measure YKL-40 levels. Patients were divided into three groups: hepatocellular carcinoma (HCC), cholangiocarcinoma (CCA), and end-stage liver disease (ESLD) without malignancies. The Model for ESLD (MELD) score was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Elevated serum YKL-40 is found in a subset of patients with nonmalignant diseases characterized by inflammation and/or tissue remodeling [19]. Previous study has demonstrated that serum YKL-40 level has little utility as a cross-sectional screening tool for hepatobiliary malignancies [20]. Furthermore, serum YKL-40 may not serve as a serum biomarker for HCC because it cannot distinguish HCC from cirrhosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum YKL-40 is found in a subset of patients with nonmalignant diseases characterized by inflammation and/or tissue remodeling [19]. Previous study has demonstrated that serum YKL-40 level has little utility as a cross-sectional screening tool for hepatobiliary malignancies [20]. Furthermore, serum YKL-40 may not serve as a serum biomarker for HCC because it cannot distinguish HCC from cirrhosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that YKL-40 is expressed by monocytes/macrophages in peripheral blood and synovial tissue [27][28][29][30][31]. Although the exact physiological function of YKL-40 is unknown, the results of clinical studies in community-acquired pneumonia, active rheumatoid arthritis, hepatic fibrosis, breast cancer, colorectal cancer, and human glioma have disclosed that serum levels of YKL-40 are correlated with the severity of disease [5][6][7][8][9][10][11][12][13]. Moreover, high levels of YKL-40 in serum and cerebrospinal fluid independently predict death in patients with pneumococcal bacteremia and purulent meningitis, respectively [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between the severity of the disease state and the levels of YKL-40 in either cerebrospinal fluid or sera of patients with a variety of pathological conditions has been demonstrated in the recent clinical studies, and most have speculated that YKL-40 might be a valuable biochemical marker of inflammation, similar to C-reactive protein [5][6][7][8][9][10][11][12][13][14][15]. YKL-40 can also be expressed in astrocytes and may take part in acute neuroinflammation [16][17][18].…”
Section: Introductionmentioning
confidence: 93%
“…The results of YKL40 assessment are in line with results of Yang et al, Ringsholt et al, and Johansen et al who illustrated the cancer progression that depends on the interplay between cancer cells and their microenvironment, particularly cells in the surrounding extracellular matrix. [32][33][34] It has been established that tumor-associated macrophages and leukocytes play important roles in tumor growth and metastasis because they produce growth and angiogenic factors, chemokines, metalloproteinases, and other extracellular matrix-degrading enzymes. Previous studies have shown that YKL40 is expressed and secreted by activated neutrophils and macrophages, indicating that YKL40 may play a role in the inflammatory process around the tumor, stimulating angiogenesis, and remodeling of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Recent immunohistochemical analyses of biopsies from HCC patients demonstrated that overexpression of YKL40 was observed in primary HCC and their matched metastatic tumors. 32 Golgi phosphoprotein 2 (GOLPH2) is a resident Golgi type-II membrane protein upregulated in liver disease. GP73 function is presently unknown.…”
Section: Discussionmentioning
confidence: 99%